Susanna „im Garten“ Eine feministisch-intertextuelle Lektüre der Susannaerzählung (lectio difficilior, 2008)
The garden is a central motif in the Old Testament story of Susanna (Daniel 13). It reveals a lot about the gender issues of the story and provides insight into the different constructions of gender in the two versions of the text: the older Septuagint (= LXX) and the younger Theodotion (= Th) version. The following article offers an intertextual reading of the two versions of the story. With regard to the garden motif as a central metaphor of the text, Genesis 2-3 and the Song of Songs are focused on as important reference texts. The intertextual readings show that the older LXX version can be read as an objection against misogynist arguments of the Hellenistic-Roman period. But while the older LXX version can be understood as a harsh critique of patriarchal values, the Th version emphasizes traditional role images of women and tames the subversive tendency that the LXX version presented. In the light of these results, the long ignored LXX version should be brought back into the centre of discussion.